Mitochondrial processing peptidases. - Gakh, O.; Cavadini, P.; Isaya, G. (Biochimica et Biophysica Acta, 2002)
Three peptidases are responsible for the proteolytic processing of both nuclearly and mitochondrially encoded precursor polypeptides targeted to the various subcompartments of the mitochondria. Mitochondrial processing peptidase (MPP) cleaves the vast majority of mitochondrial proteins, while inner membrane peptidase (IMP) and mitochondrial intermediate peptidase (MIP) process specific subsets of precursor polypeptides. All three enzymes are structurally and functionally conserved across species, and their human homologues begin to be recognized as potential players in mitochondrial disease.